SINTASAN DAN PERFORMA PERTUMBUHAN GLASS EEL (Anguilla bicolor bicolor) YANG DIPELIHARA DENGAN INTENSITAS CAHAYA BERBEDA - ERI SETIADI; Mulyana; Fajrian R A (Universitas Djuanda, 2021)
Typical constraints on eel cultivation are high mortality and slow growth rates. The purpose of this study was to determine the best light intensity for the increase in the survival rate and growth of glass eel (Anguilla bicolor bicolor). This research was conducted at Multi-Species Hatchery (MSH) Environmental Technology Research Installation and Toxicology of Freshwater Aquaculture Cibalagung, Bogor City. The research design used is a Complete RandomIzed Plan (RAL) of four treatments and three replication. Treatment A (250 Lux), treatment B (500 Lux), treatment C (750 Lux), treatment K (Without light intensity). Glass eel is kept for 50 days. The parameters and data analyzed statistically include specific growth rate (SGR), absolute length growth, absolute weight growth and survival rate (SR). The data is analyzed using a variety analysis (ANOVA). If obtained, a significant result (P<0.05) is conducted Duncan multiple range test. In addition, water quality parameters (DO, temperature and pH) are descriptively analyzed. Based on the results of the experiment, light affects the growth of both length and weight. The optimal light intensity for long growth and weight loss, i.e. C (750 Lux) treatment, produces the highest value and differs markedly from the A (250 Lux), B (500 Lux) and K (No light intensity) treatments in absolute weight growth parameters (0.37± 0.01 g), the rate of growth of specific weights (1.76±0.01 % / day), the total length (1.8±0.14 cm) and the specific length growth rate (3.41±0.05 % / day). However, for the highest contention obtained in treatment K (without light intensity) with a value of 66%, the value produced a result that differed markedly from other treatments.